Innovation in learning akidah and akhlak for Gen Z at MA Hamzanwadi NW Pancor - Wakib Kurniawan; M. Agus Nurahman; Junaidi Junaidi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Akidah Akhlak learning in Madrasah Aliyah has an important role in shaping student character according to Islamic values. However, challenges arise when the millennial generation who are familiar with technology and active learning patterns show disinterest in conventional learning methods. This study aims to identify the characteristics of the millennial generation at Hamzanwadi Madrasah Aliyah, develop relevant Akidah Akhlak learning innovations, and analyse their effectiveness in improving students' understanding and practice of Islamic values. The research method used is descriptive qualitative with observation, interviews, and documentation as data collection techniques. The results show that technology-based approaches, such as the use of interactive media and project-based learning, are able to increase students' interest in learning. Contextualised learning that is relevant to students' daily lives also proved effective in instilling Akidah Akhlak values. The study recommends continuous development in technology-based learning innovations and active collaboration between teachers, students and parents to strengthen learning outcomes.